In vitro and In vivo oxidation and cleavage products of tocols: From chemical tuners to "VitaminEome" therapeutics. A narrative review. (October 2022) - Khallouki, Farid; Saber, Somayya; Bouddine, Toufik; Hajji, Lhoussain; Elbouhali, Bachir; Silvente-Poirot, Sandrine; Poirot, Marc
Abstract: Vitamin E components and vitamin E oxidation products (VEOP) define the "vitaminEome". VEOP are produced through biological and chemical processes. They are found at low concentrations in vivo and may play particular biological functions linked with chemoprevention and inflammatory processes. Much data have been reported leading to more insight into VEOP. VEOP are generated through peroxy-radical generating systems and via reactive oxygen and nitrogen species as well as enzymatically by a variety of enzymes. In vivo, VEOP and their catabolites may reach the blood circulation and display physiological properties. This narrative review expands upon parent vitamin E chemistry as well as VEOP chemical concepts. The in vitro and in vivo routes by which they can be generated are exhaustively approached. Finally, we will discuss therapeutic and chemopreventive opportunities that VEOP offer with a special focus on their cytotoxic and anti-inflammatory functions. Graphical abstract: Image 1 Highlights: Vitamin E compounds act as antioxidants in different systems through different mechanisms. Vitamin E oxidation product (VEOP) formation is affected by several intrinsic and extrinsic factors. VEOP could be used as markers for several debilitating diseases. VEOP are associated with potent anti-inflammatory and cytotoxic activities.